Influence of upper-limb muscle strength on the repeated change of direction ability in international-level wheelchair basketball players - Iturricastillo, A.; Garcia-Tabar, I.; Reina, R.; Garcia-Fresneda, A.; Carmona, G.; Perez-Tejero, J.; Yanci, J. (Research in Sports Medicine, 2022)
This study aims 1) to compare repeated change of direction ability (rCODA) and bench press (BP) between low (A category, =2.5) and high (B category, =3.0) sport classes and 2) to analyse the relationships between rCODA and BP performance in a sample of wheelchair basketball (WB) players. Seventeen world-class WB players volunteered participated in this study. All the players undertook two tests: the repeated (x12) Modified Agility T-test (rMAT) to measure the rCODA and the movement velocity in a BP test. No significant differences were observed between categories in the rMAT and BP. For the total sample, BP variables with a mean propulsive velocity of 1 m·s-1 (V1LOAD) largely correlated with all the full rMAT outcomes (r>-0.625; p<0.05). Having a better BP could be favourable to perform repeated efforts and this seems particularly relevant in fatigue conditions, and especially for the B category players.